Implementasi Gim Si Komdig’s Journey untuk Meningkatkan Motivasi dan Kemandirian Belajar di Masa Pandemi Covid-19 - Lies Yulianto (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
This classroom action research tries to increase the motivation and learning independence of students by implementing the game Si Komdig's Journey as a learning medium in learning Simulation and Digital Communication subjects. The study was conducted on 32 students online as a impact of the Covid-19 pandemic. This research was conducted in 2 cycles, each of which consisted of 3 online meetings. The results showed an increase in the motivation and learning independence of students from 39% in cycle 1 to 70% in cycle 2. This research concludes that the implementation of the game Si Komdig's Journey as a learning medium for Simulation and Digital Communication can increase motivation and learning independence.